Early Childhood Malnourishment and its Associated Factors - Uttarakhand - Pratiti Haldar; Lekha Viswanath; Ashok Kumar Srivastava (Indian Journal of Forensic Medicine & Toxicology, 2022)
Malnutrition, a word which seems to shake our roots and disturb our future. Today the underdevelopedand many developing countries are battling this threat in many ways. The reason behind malnutrition isthe determinants which make it prevail in our neighborhood and our country on the whole. Malnutritionpossess a very serious threat to the future of our country especially the children between (1 – 3) years ofage. This paper attempts to identify the existing prevalence of malnutrition in Uttarakhand, to explorethe predisposing factors contributing to it in under five children and compare the prevalence with theselected neighboring states. An in – depth survey of all the related literatures and published articles in theselected area was made. It has been reported in recent times about the hike in India’s hunger problemsand the number of reported cases of stunting and wasting has also rocketed though underweight hasslightly reduced. The only way to curb malnutrition is by; breaking the shackles of the determinants,thorough regular surveys and screenings, improved and adequate health care services, reaching out tothe needy and spreading awareness among the masses.